Affective Deception: Experiencing Genderplay in Louisa May Alcott - Ralph J. Poole (European Journal of American Studies)
The essay attempts to theorize affective responses to a selection of Louisa May Alcott’s texts. Little Men, Moods, “Enigmas ,” and “My Mysterious Mademoiselle” all feature scenes of cross-gender play and revolve around deception due to the play on stereotypical gender expectations. I am interested in how this deception affects the recipients, which includes besides the characters of the stories also the reader.